Simultaneous nitrogen and sulphur removal effect and functional bacteria of sulfur-driven autotrophic denitrification ASBR process - YAN Hua; GUO Changzi; ZHAO Wanqin; ZHANG Xuli; HAN Yi; WANG Yixu (Gongye shui chuli)
In this paper, the influence factors of nitrogen and sulphur removal effect and main functional bacteria were investigated in a sulfide autotrophic denitrification-anaerobic sequencing batch reactor(SDAD-ASBR). The results showed that when n(S)/n(N)(recorded as S/N) was 1, and the influent S2- and NO3--N were 300 mg/L and 131.25 mg/L, respectively, there was no nitrite formation, and the sulfides and nitrates removal rates were 99.97% and 84.34%, respectively. However, as the S/N was reduced, the concentration of nitrite in the effluent increased. The hydraulic retention time(HRT) had a significant effect on the removal of nitrate, but had little effect on the sulphide removal. When HRT was shortened from 12 h to 2.4 h, the removal rates of sulfide were all above 99%, while the removal rate of nitrate decreased from 93.14% to 77.04%. The main functional genera for nitrogen and sulphur removal in the system were Exiguobacterium, Clostridium, Bacillus, Thiobacillus and Sphingomonas.